Analisis Faktor-Faktor yang Mempengaruhi Motivasi Belajar Siswa Kelas Rendah di SD Sumberadi 1 - Permatasari, Orin (STKIP PGRI SUMENEP, 2025)
This study aims to analyze factors influencing the learning motivation of lower-grade students at SD Sumberadi 1. The research explores aspects such as lack of focus, indifference to assignments, dominance of extrinsic motivation, unengaging teaching methods, limited parental support, peer influence, and an unfavorable classroom atmosphere. A descriptive qualitative approach was used, with data collected through in-depth interviews involving two teachers from lower and upper grades. Thematic analysis identified the main factors affecting motivation and strategies applied by teachers. Results show that extrinsic motivation dominates student behavior. Influencing factors include the classroom environment, teaching approaches, and parental involvement. To boost motivation, teachers employed educational games, appreciation, and concrete learning media. The study highlights the importance of collaboration between schools and parents in creating a supportive atmosphere at school and home. These findings are expected to provide insights and recommendations to improve students’ motivation through more effective and holistic educational practices.